Pelatihan Penulisan Karya Ilmiah dan Publikasinya pada Jurnal Ilmiah Bereputasi untuk Meningkatkan Kompetensi Mahasiswa Pendidikan Fisika Universitas Islam Negeri Mataram: (Training on Scientific Writing and Publication in Reputable Scientific Journals to Improve the Competence of Physics Education Students Universitas Islam Negeri Mataram) - Lalu Ahmad Didik Meiliyadi; Kurniawan Arizona; Muh. Wahyudi; Sunandar Asma'ul Hadi (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Scientific paper training has been conducted for students of the physics tadris study program at the faculty of tarbiyah and keguruan, Mataram State Islamic University. The method used in this training activity is Participatory Action Research (PAR). In general, the training activities were carried out in 4 stages, namely preparation, socialization, implementation and evaluation and reflection. Training activities have been carried out well. Based on the activity evaluation questionnaire, it shows that most participants are satisfied and enthusiastic in carrying out the training. The resource persons presented have high competence in writing scientific papers. The facilities provided are also adequate in the form of software and materials. However, the training time was not long enough. This is because it takes time to provide habituation for participants so that continuous training is needed so that participants can get good results when writing scientific papers.